Cost Study of a Cluster Randomized Trial on a Clinical Decision Rule Guiding Antibiotic Treatment in Children With Suspected Lower Respiratory Tract Infections in the Emergency Department. Issue 11 (November 2020) - van de Maat, Josephine; van der Ven, Michaël; Driessen, Gertjan; van Wermeskerken, Anne-Marie; Smit, Frank; Noordzij, Jeroen; Tramper-Stranders, Gerdien; Obihara, Charlie; Punt, Jeanine; Moll, Henriette; Polinder, Suzanne; Oostenbrink, Rianne
Abstract : Background: Children with fever and respiratory symptoms represent a large patient group at the emergency department (ED). A decision rule-based treatment strategy improved targeting of antibiotics in these children in a recent clinical trial. This study aims to evaluate the impact of the decision rule on healthcare and societal costs, and to describe costs of children with suspected lower respiratory tract infections (RTIs) in the ED in general. Methods: In a stepped-wedge, cluster randomized trial, we collected cost data of children 1 month to 5 years of age with fever and cough/dyspnea in 8 EDs in The Netherlands (2016–2018). We calculated medical costs and societal costs per patient, during usual care (n = 597), and when antibiotic prescription was guided by the decision rule (n = 402). We calculated cost-of-illness of this patient group and estimated their annual costs at national level. Results: The cost-of-illness of children under 5 years with suspected lower RTIs in the ED was on average [Euro sign]2130 per patient. At population level this is [Euro sign]15 million per year in The Netherlands ([Euro sign]1.7 million/100, 000 children under 5). Mean costs per patient in usual care ([Euro sign]2300) were reduced to [Euro sign]1870 in the intervention phase ( P = 0.01). Main cost drivers were hospitalization and lost parental workdays. Conclusions: Implementation of a decision rule-based treatment strategy in children with suspected lower RTI was cost-saving, due to a reduction in hospitalization and parental absenteeism. Given the high frequency of this disease in children, the decision rule has the potential to result in a considerable cost reduction at population level. Abstract : Supplemental Digital Content is available in the text.